Effect of PRPSOL soil conditioner on the physical status of the soil in conventional and reduced tillage systems - Szűcs, Lilla; Tuba, Géza; Zsembeli, József (Acta Agraria Debreceniensis, 2014)
The effect of PRP-SOL soil conditional on soil compaction, moisture content and bulk density is studied in a long-term soil cultivation experiment from 1997 on a heavy textured meadow chernozem soil, in reduced and conventional tillage at Karcag Research Institute. Our investigations were made in the vegetation period of corn, in June and after harvesting, on stubble. Soil compaction was measured with a penetrometer, the actual moisture content was determined by gravimetric method. The bulk density values of the regularly cultivated soil layer of 0–10 and 10–20 cm depths were defined from undisturbed soil samples. We established that after 3 years the application of the soil conditioner has positive effect on soil compaction and moisture status of the top layer in the reduced tillage system. We could not figure out this positive effect in the case of conventional tillage.